Scaling circular bio-economy solutions in refugee settings: a peer-to-peer capacity building approach - Gebrezgabher, Solomie A.; Gitau, J.; Kinyua, M.; Acanakwo, E. F.; Adam-Bradford, A.; Mendum, R.; Njenga, M. (International Water Management Institute, 2024)
Circular bio-economy approaches offer sustainable solutions to address chronic food insecurity, energy poverty, and environmental degradation in refugee and host communities across East Africa. In response, the RRR in Refugee Settlements in Africa project has implemented nature-based interventions such as home gardens, agroforestry using household greywater, and the recovery of biomass for fuel and compost across refugee settlements in Ethiopia, Kenya, and Uganda. A gender-inclusive peer-to-peer capacity-building model was central to the project’s scaling strategy. This involved stakeholder engagement, the co-development of training manuals, and the establishment of a decentralized Training of Trainers (ToT) system to equip local community facilitators with practical knowledge and skills. These facilitators trained over 3,600 households directly and reached approximately 200,000 individuals indirectly. Training focused not only on technical applications but also on entrepreneurial skills, enabling participants to create income-generating ventures through vegetable production and briquette sales. Educational outreach, demonstration sessions, and ongoing technical backstopping were critical to reinforcing learning and bridging implementation gaps. Although circular bio-economy concepts were new to many participants, the project's hands-on approach, context-specific materials, and local engagement enabled adoption and resilience-building. Lessons emphasize the importance of continuous stakeholder involvement, inclusive facilitation, and integrated support systems to ensure long-term impact and scalability.